2016
DOI: 10.1016/j.paid.2016.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Moral Foundations Questionnaire in Turkey and its relation to cultural schemas of individualism and collectivism

Abstract: Although Moral Foundations Theory (MFT) is claimed to be universally applicable, the data brought to bear in its support come from a self-selected population with mostly English-speaking participants. To the best of our knowledge, the theory has not been hitherto tested in a predominantly Muslim country with non-western moral and religious sensibilities. In Study 1, we replicated previous findings using Turkish participants by showing through confirmatory factor analyses that the 5-factor structure of MFT prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 37 publications
5
68
0
9
Order By: Relevance
“…La TFM propone una estructura de cinco fundamentos morales, innatos y universales, a partir de los cuales cada cultural desarrolla su sistema moral (Graham et al, 2013). La validación empírica por los autores de la TFM (Graham et al, 2011) y otros investigadores (Davies et al, 2014;Silvino et al, 2016;Vainio & Mäkiniemi, 2016;Yilmaz et al, 2016) se ha desarrollado principalmente a través de modelos de análisis factorial confirmatorios, los cuales no han tenido indicadores robustos. Este estudio es el primero en aplicar la TFM en una muestra chilena, lo que implica las limitaciones para generar el marco de este contexto.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La TFM propone una estructura de cinco fundamentos morales, innatos y universales, a partir de los cuales cada cultural desarrolla su sistema moral (Graham et al, 2013). La validación empírica por los autores de la TFM (Graham et al, 2011) y otros investigadores (Davies et al, 2014;Silvino et al, 2016;Vainio & Mäkiniemi, 2016;Yilmaz et al, 2016) se ha desarrollado principalmente a través de modelos de análisis factorial confirmatorios, los cuales no han tenido indicadores robustos. Este estudio es el primero en aplicar la TFM en una muestra chilena, lo que implica las limitaciones para generar el marco de este contexto.…”
Section: Discussionunclassified
“…Graham et al (2013; Señalan que los fundamentos de daño/cuidado y de justicia/ engaño son fundamentos centrados en preservar la individualidad de la persona; mientras que los otros tres fundamentos son de cohesión social, ya que permiten a las personas permanecer juntas en grupos e instituciones grandes. Diferentes estudios han señalado la validez empírica de la TFM, utilizado para ello el Análisis Factorial Confirmatorio (CFA) para la propuesta de los cinco fundamentos morales, así como para la agrupación de los fundamentos individualizantes y de cohesión grupal (Davies, Sibley, & Liu, 2014;Graham et al, 2011;Iurino & Saucier, 2018;Nilsson & Erlandsson, 2015;Silvino et al, 2016;Vainio & Mäkiniemi, 2016;Yilmaz, Harma, Bahçekapili, & Cesur, 2016). Sin embargo, los mismos autores reconocen que los índices estadísticos de bondad de ajuste no han sido robustos (Graham et al, 2011;Iurino & Saucier, 2018).…”
Section: La Teoría De Los Fundamentos Moralesunclassified
“…Confirmatory factor analysis of this data suggested that MFT's fivefactor model provided a better fit; but the size of the improvement was marginal, and more importantly, none of the resulting five-factor models exhibited a conventionally 'acceptable' model fit (CFIs 0.88; Table 10; Graham et al, 2011). Yilmaz, Harma, Bahcekapili, & Cesur, 2016), as well as a 27 country study using the short-form MFQ (CFIs 0.70; Iurino & Saucier, submitted), all suggest a similar pattern. For this reason, an alternative two-factor model -consisting of an 'individualising' domain of Care and Fairness, and the 'binding' domain of Ingroup, Authority and Purity -is typically used in research (for example, see: Lewis & Bates, 2010;Smith, Alford, Hibbing, Martin, & Hatemi, 2016).…”
Section: The Structure Of Moralitymentioning
confidence: 92%
“…Recent work however, suggests that human morality is comprised of five distinct domains (or foundations) of moral concern: care, fairness, sanctity, in-group loyalty, and respect for authority (Graham et al, 2011(Graham et al, , 2009Haidt & Joseph, 2008). Each of these distinct values are widely held across cultures (Graham et al, 2011;Yilmaz, Harma, Bahçekapili, & Cesur, 2016), and are thought to correspond to different virtues and violations (c.f. Schein & Gray, 2017 for an alternative monist account of morality).…”
Section: Morality Is Multifaceted and Sometimes Values Competementioning
confidence: 99%